Pre-Marital Assistance of Ikatan Pelajar Putri Nahdlatul Ulama (IPPNU) Metro through Guidance Services Group - Ika Ariyati; Rina Mida Hayati; Uswatun Khasanah; Muhammad Alridho Lubis (International Journal of Community Engagement Payungi, 2023)
Marriage is one of the developmental tasks of early adulthood. The tendency of individuals to have families is a genetically inherited instinct. Living together between individuals is not an easy matter, because everyone has a different background so that differences in character, perspective and decision-making become a challenge in itself. Frequently these differences become conflicts in marriages that lead to divorce. The article aimed to conduct pre-marital assistance through Group Guidance services as preventive efforts to minimize divorce rates in the future. Pre-marital guidance was given to 10 Metro City IPPNU cadres who had entered early adulthood. In this service, The method uses Participatory Action Research (PAR). The result of the dedication is that pre-marital guidance needs to be given to individuals who enter early adulthood long before marriage is carried out so that insight into knowledge, understanding and skills can really be prepared carefully.